Mathématiques
lolololol1235684
14

développer et réduire A=  -7(3x + 5) + 4(-2x +3) B=  2(-3x -1) - 4 (3-x) C=  -7(4x-3) + 3(5-x) D=  2x +3 -(6x - 7) E= - 5 (3-4x) +(-15x + 7) F=  -4x(2x +7) + x(5 + 7x) G=  - 2X(-3x-5) -5x(2x -1)

+1
(1) Réponses
louise74

Bonsoir, [latex]A= -7(3x + 5) + 4(-2x +3)\\A= -21x -35 -8x+12\\\boxed{A=-29x-27}\\\\ B= 2(-3x -1) - 4 (3-x)\\B=-6x-2-12+4x\\\boxed{A=-2x-14}\\\\C= -7(4x-3) + 3(5-x)\\C=-28x+21+15-3x\\\boxed{C=-31x+36}\\\\D= 2x +3 -(6x - 7)\\D= 2x +3 -6x +7\\\boxed{D=-4x+11}[/latex] [latex]E= - 5 (3-4x) +(-15x + 7)\\E=-15+20x-15x+7\\\boxed{E=5x-8}\\\\F= -4x(2x +7) + x(5 + 7x)\\F=-8x^2-28x+5x+7x^2\\\boxed{F=-x^2-23x}\\\\G= - 2x(-3x-5) -5x(2x -1)\\G=6x^2+10x-10x^2+5x\\\boxed{G=-4x^2+15x}[/latex]

Ajouter une réponse